Burden among caregivers of stroke patients in Kelantan - Abdul Hadi, Azwanis (IIUM Press, 2017)
Studies have shown that caregiving is associated with high burden that could affect caregivers’ mental and physical wellbeing. Unfortunately, caregivers are often overlooked even by healthcare professionals. With the rise of our elderly population and morbidity from stroke, there is a need to assess burden among family caregivers in our society. This study was carried out to determine the level of burden among caregivers of stroke patients attending Hospital Universiti Sains Malaysia in Kelantan and to evaluate the possible risk factors associated those with burden. A total of 116 caregivers of stroke patients were interviewed. The participants were recruited from the Klinik Rawatan Keluarga in Hospital Universiti Sains Malaysia. Caregivers were assessed for the level of burden using the Zarit Burden Interview. The mean burden score among the caregivers was 25.42 (SD 6.45). The minimum burden score is 11 and the maximum score is 49. This study significantly found that caregivers who look after bedbound patients have higher level of burden. While caregiver burden is lower with higher household income and among caregivers who have secondary or tertiary education level. Factors that affect caregiver’s burden such as the condition of the patient, caregiver’s education level and household income should be taken into account in the evaluation of caregivers of stroke patients.